The Secret of the Popularity of Rashi’s Commentary on the Torah - Viezel, Eran (The review of rabbinic Judaism, 2014)
How can we account for the popularity of Rashi’s commentary on Torah? Scholars have suggested that Rashi’s personality and his public and literary activities, on the one hand, and the special style of his commentary, on the other, account for the popularity of the commentary. The author proposes that in addition to these factors, it was a unique methodology that caused Rashi’s Torah commentary to become so universally loved: Rashi explained the Torah, above all, by means of aggadot meyashevot, i.e., aggadot that fill gaps in the text but preserve the sequence and meaning of the narrative plot. As far as can be determined, there is no other exegete who invented similar criteria for selecting rabbinic aggadot. The aggada meyashevet has a unique effect upon the Torah, which can be called “thickening:” the reader enjoys the benefit of following the narrative plot, as well as interwoven and integrated subplots. Rashi’s Torah commentary creates an expanded Torah which is loved by its readers far more than the Torah itself, without the aggadot that thicken it.